Stool Xpert MTB/RIF and urine lipoarabinomannan (LAM) for diagnosing tuberculosis in hospitalized HIV-infected children - LaCOURSE, Sylvia M. (AIDS, 2018)
BACKGROUND: Tuberculosis (TB) causes substantial morbidity and mortality in HIV-infected children. Sample collection and paucibacillary nature of TB in children makes diagnosis challenging. Rapid diagnostic tools using easily obtained specimens are urgently needed. METHODS: Hospitalized, HIV-infected children ≤12 years enrolled in a randomized controlled trial (NCT02063880) comparing urgent to post-stabilization ART initiation in Kenya underwent TB evaluation. At enrollment, sputum or gastric aspirates (GA) were collected for TB culture and Xpert, stool for Xpert, and urine for lateral flow lipoarabinomannan (LAM). When possible, a second sputum/GA culture was obtained. Stool Xpert and urine LAM performance were compared to reference sputum/GA culture. RESULTS: Among 165 HIV-infected children, median age was 24 months (IQR 13–58), median CD4% was 14.3% (IQR 8.9–22.0%), and 114 (69.5%) had severe immunosuppression. Thirteen (7.9%) children had confirmed TB (positive culture and/or Xpert). Sputum/GA Xpert, stool Xpert, and urine LAM sensitivities were 60% (95% CI 26–88%), 63% (95% CI 25–92%), and 43% (95% CI 10–82%), respectively. Specificity was 98% (95% CI 94–100%) for sputum/GA Xpert, 99% (95% CI 95–100%) for stool Xpert, 91% (95% CI 84–95%) for urine LAM. Stool Xpert and urine LAM sensitivity increased among children with severe immunosuppression (80% [95% CI 28–100%] and 60% [95% Cl 15–95%]). CONCLUSIONS: Stool Xpert had similar performance compared to sputum/GA Xpert to detect TB. Urine LAM had lower sensitivity and specificity, but was higher among children with severe immunosuppression. Stool Xpert and urine LAM can aid rapid detection of TB in HIV-infected children using easily accessible samples.